The Role of Islamic Education in the Formation of the Nation's Character - Muh. Idris; Merdi F. Mamonto; Sabil Mokodenseho; Wily Mohammad (West Science Islamic Studies, 2023)
This research investigates the role of Islamic education in shaping the national character among students in Madrasah Aliyah Negeri (MAN) schools in Indonesia. Employing a quantitative approach, the study surveyed a diverse sample of students across different regions, focusing on the perceived impact of Islamic education on moral values and character development. Results indicate a highly positive perception among participants, with the majority acknowledging the significant influence of Islamic teachings on character traits aligned with the Pancasila principles. The study also reveals regional variations, suggesting that the impact of Islamic education on national character may be nuanced by geographic context. The findings contribute to the ongoing discourse on character formation within the unique educational setting of MAN schools, providing valuable insights for educational policymakers and practitioners.